2016
DOI: 10.1097/01.ogx.0000481796.11218.bd
|View full text |Cite
|
Sign up to set email alerts
|

Limited Clinical Utility of Non-invasive Prenatal Testing for Subchromosomal Abnormalities

Abstract: The use of massively parallel sequencing of maternal cfDNA for non-invasive prenatal testing (NIPT) of aneuploidy is widely available. Recently, the scope of testing has increased to include selected subchromosomal abnormalities, but the number of samples reported has been small. We developed a calling pipeline based on a segmentation algorithm for the detection of these rearrangements in maternal plasma. The same read depth used in our standard pipeline for aneuploidy NIPT detected 15/18 (83%) samples with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 15 publications
3
47
0
Order By: Relevance
“…Although this is a single case, our findings are in line with the recent academic validation study by Lo et al , suggesting that rare microdeletions may not be robustly detected using similar genome‐wide counting‐based cfDNA assays, particularly in samples with relatively low fetal cfDNA fraction. Wolf‐Hirschhorn syndrome is associated with terminal deletions of 4p as small as 2 Mb .…”
Section: Casesupporting
confidence: 86%
See 1 more Smart Citation
“…Although this is a single case, our findings are in line with the recent academic validation study by Lo et al , suggesting that rare microdeletions may not be robustly detected using similar genome‐wide counting‐based cfDNA assays, particularly in samples with relatively low fetal cfDNA fraction. Wolf‐Hirschhorn syndrome is associated with terminal deletions of 4p as small as 2 Mb .…”
Section: Casesupporting
confidence: 86%
“…In the current pregnancy, this assay was reported as normal despite the presence of the same unbalanced translocation in the fetus. To our knowledge, while false negative results have been found in the academic setting, and are to be expected in any screening assay, such false negative results from commercially available microdeletion testing have not yet been reported in the literature. Awareness of the limitations of these assays is important both for provider education and for offering laboratories.…”
Section: Casementioning
confidence: 84%
“…The inclusion of increasingly rare conditions in cfDNA panels will inevitably increase the false positive rate of cfDNA screening, potentially limiting the primary benefit of cfDNA screening in reducing the need for diagnostic testing. 37, 38 This may be especially problematic in low resource areas with limited access to the skilled diagnostic practitioners required to confirm cfDNA results. Significant differences exist between these newly added conditions and the currently-screened trisomies, leading some to argue that highly disparate clinical realities are now being inappropriately lumped together and raising additional challenges to patient counseling.…”
Section: Women’s Health and Gender In Contextmentioning
confidence: 99%
“…Recent studies have shown that with NIPT, also other autosomal aneuploidies (other than trisomy 13, 18 and 21) and even segmental chromosomal aberrations can be detected . Further validation and clinical studies in larger cohorts are however warranted to assess the added value, sensitivity and specificity of these results …”
Section: Introductionmentioning
confidence: 99%